Aspiration pneumonia induces muscle atrophy in the respiratory, skeletal, and swallowing systems. Issue 4 (22nd May 2018) - Komatsu, Riyo; Okazaki, Tatsuma; Ebihara, Satoru; Kobayashi, Makoto; Tsukita, Yoko; Nihei, Mayumi; Sugiura, Hisatoshi; Niu, Kaijun; Ebihara, Takae; Ichinose, Masakazu
Abstract: Background: Repetition of the onset of aspiration pneumonia in aged patients is common and causes chronic inflammation. The inflammation induces proinflammatory cytokine production and atrophy in the muscles. The proinflammatory cytokines induce muscle proteolysis by activating calpains and caspase‐3, followed by further degradation by the ubiquitin‐proteasome system. Autophagy is another pathway of muscle atrophy. However, little is known about the relationship between aspiration pneumonia and muscle. For swallowing muscles, it is not clear whether they produce cytokines. The main objective of this study was to determine whether aspiration pneumonia induces muscle atrophy in the respiratory (the diaphragm), skeletal (the tibialis anterior, TA), and swallowing (the tongue) systems, and their possible mechanisms. Methods: We employed a mouse aspiration pneumonia model and computed tomography (CT) scans of aged pneumonia patients. To induce aspiration pneumonia, mice were inoculated with low dose pepsin and lipopolysaccharide solution intra‐nasally 5 days a week. The diaphragm, TA, and tongue were isolated, and total RNA, proteins, and frozen sections were stored. Quantitative real‐time polymerase chain reaction determined the expression levels of proinflammatory cytokines, muscle E3 ubiquitin ligases, and autophagy related genes. Western blot analysis determined the activation of the muscle proteolysis pathway. Frozen sections determined the presence of muscle atrophy. CT scans were used to evaluate the muscle atrophy in aged aspiration pneumonia patients. Results: The aspiration challenge enhanced the expression levels of proinflammatory cytokines in the diaphragm, TA, and tongue. Among muscle proteolysis pathways, the aspiration challenge activated caspase‐3 in all the three muscles examined, whereas calpains were activated in the diaphragm and the TA but not in the tongue. Activation of the ubiquitin‐proteasome system was detected in all the three muscles examined. The aspiration challenge activated autophagy in the TA and the tongue, whereas weak or little activation was detected in the diaphragm. The aspiration challenge resulted in a greater proportion of smaller myofibers than in controls in the diaphragm, TA, and tongue, suggesting muscle atrophy. CT scans clearly showed that aspiration pneumonia was followed by muscle atrophy in aged patients. Conclusions: Aspiration pneumonia induced muscle atrophy in the respiratory, skeletal, and swallowing systems in a preclinical animal model and in human patients. Diaphragmatic atrophy may weaken the force of cough to expectorate sputum or mis‐swallowed contents. Skeletal muscle atrophy may cause secondary sarcopenia. The atrophy of swallowing muscles may weaken the swallowing function. Thus, muscle atrophy could become a new therapeutic target of aspiration pneumonia.